(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Parkinson’s disease (PD) is a chronic progressive devastative disorder of neurons characterized by a muscle rigidity, tremors, bradykinesia etc. In present scenario, it is affecting more than 1% population above 50 years of age and hence is an important concern in society. Advancement in research field in recent decades has led to upsurge the use of animals for evaluation of new drugs. Objective: In contemplation of upward trend in use of animals, PASS (prediction of activity spectra of substances), a web tool, provides an informative prediction data for different pharmacological activity of compounds without using the animals which justifies the 3R’s ethics (Reduction, Replacement, and refinement) to be followed for in vivo evaluation. Methods: For prediction of pharmacological activities of anti-parkinson compounds, canonical smiles of phytochemicals were obtained from Pubmed and used in the software for prediction of relevant pharmacological activity so that phytochemicals, showing best results can be further explored for in vivo evaluation against PD. Using PASS online software, biological activity spectra for nine different activities related to Parkinson’s disease for selected phytochemicals was predicted and compared with marketed compounds. Result: Out of selected phytochemicals, scopolamine and atropine have shown highest antiparkinsonian activities. Piperine was also found to have antiparkinsonian activity. Elaeocarpine, harmine and oxyresveratrol have found to have comparable activity for this condition. Conclusion: This article describes the utility of PASS to justify the 3R’s concept which is to be followed for the further in vivo exploration of compounds.